Beam-Steering Performance of Flat Luneburg Lens at 60 GHz for Future Wireless Communications. (2nd August 2017) - Foster, Robert; Nagarkoti, Deepak; Gao, Ju; Vial, Benjamin; Nicholls, Felix; Spooner, Chris; Haq, Sajad; Hao, Yang
Abstract : The beam-steering capabilities of a simplified flat Luneburg lens are reported at 60 GHz. The design of the lens is first described, using transformation electromagnetics, before discussion of the fabrication of the lens using casting of ceramic composites. The simulated beam-steering performance is shown, demonstrating that the lens, with only six layers and a highest permittivity of 12, achieves scan angles of ± 30° with gains of at least 18 dBi over a bandwidth from 57 to 66 GHz. To verify the simulations and further demonstrate the broadband nature of the lens, raw high definition video was transmitted over a wireless link at scan angles up to 36°.